(untitled) (TAMADDUN NURI JURNALI, 2024)
This article explores the impact of perfectionism on success and personal development. Adaptive perfectionism enhances achievements and personal growth, while maladaptive perfectionism leads to burnout and challenges in social relationships. The paper examines the role of perfectionism in academic and professional settings, its effect on social interactions, and the importance of learning from setbacks.